Headache in Caucasian patients with Moyamoya angiopathy: a systematic cohort study - Krämer, Markus; Berlit, Peter (Cephalalgia, 2017)
Background: Headache is common in patients with Moyanoya angiopathy (MMA), but usually underestimated in its management and not well characterized. Methods: A validated self-administered headache screening questionnaire and a telephone interview were used in order to investigate headache characteristics, frequency and pain intensity in a large cohort of 55 German patients with MMA. Results: Thirty-seven patients (67.3%) had suffered from headache in the past year. Headache intensity was rated 3.2?±?1.3 on a verbal rating scale from 0 to 10. Seventeen patients (47.9%) reported migraine-like headache, 10 patients (27.0%) reported tension type-like headache and 10 patients (27.0%) had a combination of both. The majority of patients with migraine-like headache (n?=?10, 58.8%) described migrainous aura. Headache frequency and intensity improved significantly after revascularization surgery; however, nine patients developed new-onset headache postoperatively. Conclusion: Headache is very common in MMA, often with a migraine-like phenotype. Tension type-like headache was also found in 27% of patients, which is a new finding that has not been reported before.